Estado nutricional y riesgo nutricional, aplicando el NRS-2002 en pacientes hospitalizados del Hospital Apoyo Iquitos-2023 - Lozano Moncada, Claudia Christina (2024)
The present study is focused on determining the nutritional status and nutritional risk by applying the nutritional screening tool NRS-2002 (Nutritional Risk Screening-2002) in hospitalized patients of the Medicine and Surgery service of the Hospital Apoyo Iquitos-2023. Method: the study had a quantitative approach and a descriptive, non-experimental, cross-sectional observational design. The sample included 369 hospitalized patients. Results: Of the sample studied by applying the NRS-2002, the nutritional status was normal (45%), followed by overweight (26%), obese (12%) and lean (17%). When nutritional risk was assessed, 79% (n=293) had no risk, 18% (n=66) had medium risk and 3% (n=10) high risk, with risk and thinness being more prevalent in medicine (26%, 13%) compared to surgery (16%, 12%). The most frequent pathologies were gastrointestinal and traumatic, cardiovascular and pneumological diseases were nutritional risk. Conclusions: These findings highlight the need to implement nutritional screening on hospital admission for the identification and timely nutritional intervention of patients at risk.